The Effect of the combination of active vestibular intervention and occupational therapy on Balance in Children with Bilateral Spastic Cerebral Palsy: A pilot randomized Controlled trial - Rassafian, Mehdi; Akbarfahimi, Nazila; Hosseini, Seyed. Ali; Shahshahani, Soheila; Karimlou, Masoud; Tabatabai Ghomsheh, Farhad (Iranian Journal of Child Neurology, 2020)
Objective This study aimed to examine the effect of the combination of active vestibular interventions and occupational therapy on balance, and the relationship between balance changes and Activity of Daily Living in school-aged children with cerebral palsy (CP). Materials & Methods Twenty-four children with Spastic CP, at level I and II according to the “Gross Motor Function Classification System aged 7-12 years were enrolled and randomly assigned into control and intervention groups. Pediatric Balance Scales, Bruininks-Oseretsky Test of Motor Proficiency II were employed to assess the functional balance changes, as well as Force Plate (during eyes closed and open) to assess the parameters of balance changes (e.g., center of pressure excursion), Activity of Daily Living was assessed by “Activity Scales for Kids (performance version)”. Participants in the intervention group received active vestibular intervention for 20 min and regular occupational therapy program for 25 min, and the control group received regular occupational therapy program for 45 min. Interventions were provided 3 d/week for 6 weeks in each group. The participants were assessed in three stages: baseline, immediately after and eight weeks after intervention. Data were analyzed by ANOVA and linear regression. Results The results demonstrated that only functional balance according to Pediatric Balance Scales scores was significantly increased in the active vestibular interventions group (p=0.02). There was no significant relationship between functional balance and Activity of Daily Living (P>0.05). Conclusion The combined administration of active vestibular interventions and occupational therapy could improve the functional balance in children with spastic CP. It may be related to the reorganization of the vestibular system with a controlled and precise application of stimuli.